Numerical simulation and experimental study of the extrusion process for rice straw powder based on EDEM - Sun, Chaoran; Ai, Wenke; Jiang, Ping; Sun, Songlin; Chen, Limei; Tan, Shaohui; Gao, Chongfeng (International Journal of Agricultural and Biological Engineering, 2025)
The application of twin-screw extrusion technology in the field of straw pretreatment is constrained by the closed nature of its structure, and the internal material flow characteristics have yet to be fully elucidated. This has resulted in a paucity of scientific theoretical support for screw configuration design. To address this issue, this study employed the discrete element method (DEM) in conjunction with physical tests to calibrate the simulation model parameters of rice straw powder. The calibration results demonstrate that the discrepancy between the simulation stacking test and the physical test results is 3.68%, thereby indicating that the simulation model parameters are accurate and reliable. Subsequently, an extrusion verification comparison test of rice straw powder was conducted. The results demonstrated that the relative errors between the simulated and actual quality in different regions ranged from 7.95% to 12.45%. This evidence substantiates the applicability and reliability of the established simulation model in simulating the extrusion process of rice straw powder. Furthermore, the variation rules of the parameters of particle motion and their correlation during the extrusion process of rice straw powder were investigated. It was found that the filling degree was significantly correlated with other parameters, and that the screw configuration had a direct influence on the filling degree. Finally, a bench test was conducted to ascertain the viability of the established simulation model in guiding the design of screw configurations. A linear regression equation was derived between the simulated power consumption and the average particle size of extruded samples under different screw configurations. The study offers a particle-scale understanding of the visualization of the extrusion process of rice straw powder and the scientific design of screw configurations, which is of great significance for the industrial application of the extrusion method. Key words: rice straw; discrete element method; twin-screw extrusion; parameter calibration; numerical simulationDOI: 10.25165/j.ijabe.20251802.9381Citation: Sun C R, Ai W K, Jiang P, Sun S L, Chen L M, Tan S H, et al. Numerical simulation and experimental study of the extrusion process for rice straw powder based on EDEM. Int J Agric & Biol Eng, 2025; 18(2): 288–298.